The Byzantine-Arab Borderland in the Light of Digenis Akritas - Mikuła, Maksymilian (Vade Nobiscum, tom XXIV/2024: Studia nad Bliskim Wschodem, 2024)
Digenis Akritas is the only Byzantine epic preserved to this day. It was most likely written in the XII century, during the reign of the Komnenian dynasty in Byzantium. The epic is divided into two parts. The first one is focused on Musur, an Arabian emir who was baptized. The second one presents the story of his son, the legendary warrior Basil Digenis Akritas. In the article the author considers how the Byzantine-Arabian border was portrayed before 1071, that is at the time when the action of the epic takes place. He analyzes for example such issues as the importance of religion for the borderland population, the role of the military aristocracy and the importance and the causes of combat in the society of the discussed area. The historian compares the information from epic with other sources, that is De ceremoniis of Constantine Porphyrogenitus and Concilia et Narrationes of Kekaumenos. At the end of the article, he presents conclusions on how the borderland is depicted in the epic, and if it provides reliable information about this territory.